The Productivity Commission Inquiry Report: The market for retail tenancy leases in Australia - Webb, Eileen (Butterworths, 2009)
The Productivity Commission report into the market for retail tenancy leases in Australia was made available generally on 27 August 2008. This article outlines the rationale for, and background to, the inquiry and discusses the findings and recommendations of the Final Report.To the PC (Productivity Commission) anything that interferes with a landlord’s ability to exploit their market power is by their definition ‘inefficient’ — therefore any ‘prescriptive legislation’ that attempts to put the brakes of their exploitation of market power — must be removed. Therefore, tear up all state Retail Leasing Acts, and keep the Trade Practices Act a loophole ridden mirage, and let’s go back to the law of jungle, as this is ‘more efficient’.1In July 2007, the then Commonwealth Treasurer2 requested that the Productivity Commission3 ‘undertake an inquiry into the market for retail tenancy leases in Australia’. The inquiry was said to be a response to ‘a range of concerns about aspects of retail tenancy raised with the Australian Government’.4 After a period of consultation,5 a draft report was released in November 2007.6 Further submissions were received7 and the Final Report8 was provided to the Federal parliament on 31 March 2008.9 The report was released generally on 27 August 2008. The Commonwealth Government’s response to the Productivity Commission’s recommendations was generally positive, although some areas of caution were noted.This article will outline the rationale for, and background to, the inquiry, the findings and recommendations of the Final Report and provide a short commentary thereon.